Réponses

Meilleure réponse !
2014-03-02T09:26:17+01:00
A = (3 -3/4)-5/8
(12/4 -3/4) -5/8
9/4 -5/8
18/8 -5/8 = 15/8

( 3 X 3/4) X 5/8
9/4 X 5/8
45/32 

(3 -3/4) +5/8
12/4 -3/4 +5/8
9/4 +5/8
18/8 +5/8
23/8

(3 -3/4) -5/8
12/4 -3/4 -5/8
9/4 -5/8
18/8 -5/8
13/8
merci beaucoup
il est faux le premier
tu peux m aider ploup stp
2014-03-02T09:26:36+01:00
A= (3-3/4)-5/8
A=(12/4-3/4)-5/8
A=9/4-5/8
A=18/8-5/8
A=13/8



B=(3*3/4)*5/8
B=9/4*5/8
B=45/32


C=(3-3/4)+5/8
C=(12/4-3/4)-5/8
C=9/4+5/8
C=18/8+5/8
C=23/8


D= pareil que le premier...